Wireless Power Transmission for Electric Vehicle - M S Kavitha, J Jayaseelan, J S. Mohammad Sajid, K. Pravin, J. Raahul (Mathematical Statistician and Engineering Applications, 2022)
Road transportation is majorly used transportation. Usage of car is drastically increased and the need for the petrol and diesel are increased. Now days due to this effect implementation of electric vehicles was started in our country. At a public parking facility, only electric vehicles (EVs) that are parked at dedicated parking spaces with charging points can enjoy charging services. Installing a charging point at each parking slot is very expensive. As an alternative, this project proposes the novel idea in public transport facility, only electric vehicles (EVs) that can drive at dedicated with wireless charging path which can enjoy charging services. Installing a wireless charging path (WCP) as electric vehicle service road (EVSR). Laying EV service roads will be efficient for charging the EVs wirelessly while traveling. Charging mechanism of vehicles is done via WPT which reduces the requirement of cables, reduce the waiting time for also has generating system based on solar energy.